Achieving vigor in style through word order - Llanes, Violeta (Aborro) 1945-
The purpose of the study is to determine the different ways in which word order of an adjective, an adverb or the Subject-Verb-Complement pattern can be varied and still conform to grammatical rules. Also, it aims to identify a way to achieve a stylistic effect through a change in word order. The study proposed a way for English teachers to teach variations in word order as style.